Analysing the Key Causes of Road Accidents in Bangladesh - Das, Keya Rani; Adhikary, Bishnu Kumar; Barman, Linnet Riya; Khatun, Fatima; Burman, Preetilata (Journal of Business and Social Sciences Research, 2024)
Bangladesh has experienced a concerning rise in traffic accidents over time, leading to numerous unintentional deaths and injuries. To address road safety effectively, it is crucial to first focus on the factors that contribute to these crashes. The primary purpose of this article is to systematically compile and analyse the contributing factors to road traffic accidents within the geographical boundaries of Bangladesh, with a particular emphasis on finding the key determinants. To carry out this objective, the study applied fishbone diagrams and Pareto charts as analytical tools, thereby facilitating a comprehensive examination of the underlying root causes associated with road accidents in the country. According to research, untrained drivers are the leading cause of road accidents in Bangladesh, as shown by the primary data we have gathered. Furthermore, data shows that six primary factors account for 80 percent of Bangladesh’s traffic accidents. Through the enhanced consideration of these fundamental causes, the frequency of traffic accidents can be feasibly diminished, so preventing further injuries and fatalities. To reduce the frequency of road accidents, policymakers should address the major factors that cause accidents on the road.